Prevalence of depression and anxiety and stress among HIV patients in Kuantan - Abdul Hadi, Azwanis; Mohd Mustapha, Nur Syuhada; Ahmad Hafidzi, Nur Farhana; Shaari, Nur Sahira; Pasi, Hafizah (Fakulti Perubatan UNISZA, Kuala Terengganu, 2017)
Depression, anxiety and stress has been found to be present among people who are living with Human Immunodeficiency Virus (PLHIV) 1,2,3. Unfortunately, it is often missed during clinic visits. This could be a challenge to the primary care physician in managing patients in terms of their compliance to their long-term medications